Experiential Learning with STEM-Computational Thinking (STEM-CT) Approach to Develop Students’ Problem Solving Skills - Sayyidah Assadillah Almujaddid; Lia Yuliati; Hari Wisodo (Postgraduate, University of Mataram, 2025)
Future challenges for learning require students to not only master concepts, but also develop thinking skills, one of which is problem solving skills. The aim of this study was to identify the effect of Experiential Learning with STEM-Computational thinking (STEM-CT) approach on students' problem solving skills. This research falls under a quasy experiment type with pretest-posttest control group design involving 60 students in 11th grade, especially on static fluid topic. The author collected quantitative data through pre-test and post-test, to assess the difference in students' problem solving skills between the experimental and control groups. Data analysis was carried out using parametric statistics, namely independent sample t-test, and obtained sig. 2 tailed of 0.001 which meets p < 0.05, so it can be concluded that there are differences in problem solving skills between the control class and the experimental class, after being given different treatments. The average N-Gain scores of the experimental class is also higher than control class. It indicates the effect of experiential learning with STEM-CT approach on students' problem solving skills. In the future, more in-depth research is needed related to the effect of experiential learning on various other thinking skills, especially in physics learning.